Źródła i przedmiot nauczania katechetycznego w ujęciu prawa kanonicznego - Adamczyk, Jerzy (Poznańskie Studia Teologiczne, 2016)
The following article deals with the sources and subject of religious teaching from the canon point of view. Canon Law Code 760 specifies the Holy Bible as the first and primary source of religious education. The next fundamental source of cathesis is Tradition, then, the liturgy and the Magisterium and Church life. The subject of word ministry (religious education) should be the mystery of Christ presented entirely and faithfully, taking the law hierarchy into account.